2015
DOI: 10.1123/ijspp.2014-0381
|View full text |Cite
|
Sign up to set email alerts
|

Validity of a Trunk-Mounted Accelerometer to Measure Physical Collisions in Contact Sports

Abstract: The findings indicate that the MinimaxX S4 accelerometer can accurately measure physical-collision peak impact accelerations when data are filtered at a 20-Hz cutoff frequency. As a result, accelerometers may be useful to measure physical collisions in contact sports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…The three orthogonal acceleration signals were filtered using a 4 th -order Butterworth bandpass filter with cut-offs set at 0.1 Hz and 15.0 Hz. These frequencies were chosen to remove gravity [5,15] and noise [37,38] components, respectively. The magnitude of the instantaneous acceleration vector was calculated by taking the square root of the sum of the square of the three orthogonal accelerations [36].…”
Section: Data Analysesmentioning
confidence: 99%
“…The three orthogonal acceleration signals were filtered using a 4 th -order Butterworth bandpass filter with cut-offs set at 0.1 Hz and 15.0 Hz. These frequencies were chosen to remove gravity [5,15] and noise [37,38] components, respectively. The magnitude of the instantaneous acceleration vector was calculated by taking the square root of the sum of the square of the three orthogonal accelerations [36].…”
Section: Data Analysesmentioning
confidence: 99%
“…Previous studies investigating the concurrent validity of IMUs primarily identified external rather than internal factors affecting validity, with respect to manufacturer-provided parameters [14,15,19]. Findings clearly point towards the intensity of motion as well as the performed movement task itself affecting the IMU’s concurrent validity [14,19], with higher errors being found for high-intensity movements such as sprinting, jumping, and tackling.…”
Section: Introductionmentioning
confidence: 99%
“…However, pre-processed parameters provided within the proprietary software of tracking devices typically rely on KF-based algorithms. Even though the validity of these parameters has previously been examined, current research is mostly restricted to evaluating the resultant acceleration magnitude [14,15]. More detailed analysis in the horizontal and vertical movement planes is not typically provided by manufacturers, even though this is crucial for comprehensive and meaningful analysis of athletes’ locomotor demands during sports.…”
Section: Introductionmentioning
confidence: 99%
“…16 Unsurprisingly, spikes in accelerometer data can occur during a high-intensity acceleration or change of direction and may indeed be recorded by this equipment as an 'impact', 17 which can be incorrectly interpreted by practitioners as a collision or contact event with an opponent. 16 Although wearable microtechnology has demonstrated validity when measuring collision and impact forces during walking, running, and team sport movements, 17,18 research is yet to investigate the accuracy of a microtechnology device to distinguish between collision events and other spikes in accelerometer data during professional rugby league match-play.…”
mentioning
confidence: 99%